Tourism Destination Development Plan – A Study of Cheyyur Region as Transit Hub in Tamilnadu - C, Geetha; M, Palani (South India Journal of Social Sciences, 2025)
Tourism industry is the largest and fastest growing industry in the world. Its contribution towards economic growth is tremendous. Realising its growing importance in generating employment and its increasing contributions towards GDP, Indian government has introduced schemes like PRASHAD, Swadesh Darshan, SAATHI, Dekho Apna Desh and NIDHI. The Tamil Nadu Tourism Development Corporation is introducing new programmes for destination development in Tamil Nadu, especially rural tourism destinations which will strengthen the economy of the rural areas in Tamil Nadu, Cheyyur, an enchanting village in Chengalpattu district, is about 100 kilometers from Chennai. Cheyyur is noted for its rich heritage and culture, with potential for high-level community-based tourism in the area. Given its proximity close to both Mamallapuram to the east and Pondicherry to the west, this area may be developed as a transit tourist attraction bridging the two cities. The objective of the study is to find the tourism potentials of Cheyyur region and to understand opportunities and challenges in developing Cheyyur region as a sustainable and responsible transit tourist destination. The concluding section offers suggestions on how to leverage the opportunities to overcome the challenges in developing Cheyyur region as a transit tourist destination.